Use of electronic databases by the scientists in IITA, Ibadan, Nigeria (2012)
This paper examines the use of The Essential Electronic Agricultural Library (TEEAL), Swetswise, and JSTOR (Journal Archives) among International Institute of Tropical Agriculture scientists. Instruments used in this study were library records, interview and observation. The library records collected covered the period of five years (2006 to 2010). This paper revealed that IITA headquarters in Ibadan. Nigeria as well as other stations used the three databases. TEEAL among the three electronic databases was discovered as the most used database. Barriers to effective utilization of the electronic databases were identified and solutions were proffered.